Palladium Nanoparticles Immobilized on Nanosilica Triazine Dendritic Polymer (Pdnp-nSTDP) as Catalyst in the Synthesis of Mono-, Di-, and Trisulfides through C–S Cross-Coupling Reactions - Isfahani, Amir Landarani; Mohammadpoor-Baltork, Iraj; Mirkhani, Valiollah; Moghadam, Majid; Khosropour, Ahmad Reza; Tangestaninejad, Shahram; Nasr-Esfahani, Mahboobeh; Rudbari, Hadi Amiri (Synlett, 2014)
A wide variety of diaryl sulfides has been synthesized in excellent yields via C–S cross-couplings of aryl/heteroaryl halides with aromatic/heteroaromatic thiols in the presence of palladium nanoparticles immobilized on nanosilica triazine dendritic polymer (Pdnp-nSTDP) as a reusable catalyst under thermal conditions and microwave irradiation. Pdnp-nSTDP also showed excellent catalytic activity for the preparation of a series of di- and trisulfides with benzene, pyridine, pyrimidine, and/or 1,3,5-triazine as the central cores by one-pot multi C–S cross-coupling reactions.
Keywords: supported catalysis; palladium; cross-coupling; dendrimers; thiols